Optimization of preparation process and flavor analysis of vegetable juice fermentation broth simulating aged brine - LI Jing, ZHANG Min, YANG Jinmei, SONG Xiaoyan, REN Jingyi, HUANG Xinyue, WAN Yizhuo, WANG Wen, HU Kaidi, LIU Shuliang (Zhongguo niangzao)
In order to simulate aged brine, vegetable juice fermentation broth was prepared using radish, cucumber and tomato as raw materials and Lactobacillus plantarum P158, LYA31 and Pediococcus pentosaceus PP as fermentation strains. The fermentation conditions were optimized by single- factor experiments and orthogonal experiments. The volatile flavor compounds were analyzed by headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS), and the key volatile flavor compounds (OAV≥1) were determined by the odor activity value (OAV). The results showed that the optimal fermentation conditions for vegetable juice fermentation broth were as follows: glucose addition 2%, salt addition 2%, solid-liquid ratio 1.5∶1.0 (g∶ml), and fermentation temperature 37 ℃. Under this optimized condition, the total acid content of the vegetable juice fermentation broth was 0.81 g/100 ml, the pH value was 3.20, and the lactic acid bacteria counts were 8.59 lg (CFU/ml). A total of 26 volatile flavor compounds were detected in the vegetable juice fermentation broth, including 2 acids, 1 ester, 9 alcohols, 5 aldehydes, 4 ketones, 2 hydrocarbons and 3 others. Among them, the contents of ethanol and dimethyl disulfide were relatively high, which were 58.13 μg/kg and 41.15 μg/kg, respectively. The key volatile flavor substances were n-hexanol, linalool, crotonaldehyde, trans-2-octenal, dimethyl disulfide and dimethyl trisulfide.